Karakteristik Fisiko Kimia dan Organoleptik Bakso Vegetarian Berbasis Tempe Kacang Kedelai dan Kacang Merah (Phaseolus vulgaris L.) - Murni, Lissa; Manshur, Hanif Alamudin; Saati, Elfi Anis (Food Technology and Halal Science Journal, 2024)
Meatballs are one of the foods that are much liked by the people of Indonesia. Meatballs are generally made from meat, such as chicken, beef or fish. Vegetarians tend to consume meat analogues to replace animal flesh. Analog meat is usually made from legumes such as soybeans and red beans, where protein is an important nutrient needed by a vegetarian. Research using a simple randomized block design (RBD) with 7 treatment levels. The control treatment consisted of 50g of soybean flour and 50g of red bean flour. While the other 6 treatments used a comparison between soybean tempeh and red bean flour, namely 50:50; 55:45 ; 60:40 ; 65:35 ; 70:30 and 75:25. The results showed that the comparison of soybean tempeh and red bean flour had a significant effect on proximate levels (moisture content, ash content, fat content, protein content, carbohydrates), yield and meatball elasticity and had no significant effect on water holding capacity meatball. Treatment using 65g soybean tempeh and 35g red bean flour was the best treatment, with an average moisture content of 56.24%, ash content of 2.21%, fat content of 9.15%, protein content of 11.02%, carbohydrates 21.35%, water holding capacity 117.26%, yield 108.09%, elasticity 100.61gf, aroma 3.06 (rather like), color 3.06 (rather like), texture 3.33 (rather like) and taste 3.53 (towards like).